MHC Variants Associated With Symptomatic Versus Asymptomatic SARS-CoV-2 Infection in Highly Exposed Individuals - Castelli, Erick C.; de Castro, Mateus V.; Naslavsky, Michel S.; Scliar, Marilia O.; Silva, Nayane S. B.; Andrade, Heloisa S.; Souza, Andreia S.; Pereira, Raphaela N.; Castro, Camila F. B.; Mendes-Junior, Celso T.; Meyer, Diogo; Nunes, Kelly; et al. (Frontiers in Immunology, 2021)
Despite the high number of individuals infected by SARS-CoV-2 who develop COVID-19 symptoms worldwide, many exposed individuals remain asymptomatic and/or uninfected and seronegative. This could be explained by a combination of environmental (exposure), immunological (previous infection), epigenetic, and genetic factors. Aiming to identify genetic factors involved in immune response in symptomatic COVID-19 as compared to asymptomatic exposed individuals, we analyzed 83 Brazilian couples where one individual was infected and symptomatic while the partner remained asymptomatic and serum-negative for at least six months despite sharing the same bedroom during the infection. We refer to these as "discordant couples". We performed whole-exome sequencing followed by a state-of-the-art method to call genotypes and haplotypes across the highly polymorphic MHC region. The discordant partners had comparable ages and genetic ancestry, but women were overrepresented (65%) in the asymptomatic group. In the antigen-presentation pathway, we observed an association between HLA-DRB1 alleles encoding Lys at residue 71 (mostly DRB1*03:01 and DRB1*04:01) and DOB*01:02 with symptomatic infections, and HLA-A alleles encoding 144Q/151R with asymptomatic seronegative women. Among the genes related to immune modulation, we detected variants in MICA and MICB associated with symptomatic infections. These variants are related to higher expression of soluble MICA and low expression of MICB. Thus, quantitative differences in these molecules that modulate NK activity could contribute to susceptibility to COVID-19 by down regulating NK cell cytotoxic activity in infected individuals but not in the asymptomatic partners.